Rückzugsorte des Erzählens Muße als Modus autobiographischer Selbstreflexion - Sennefelder, Anna Karina (Mohr Siebeck, 2020)
In European cultural history, otiose leisure is regarded as the ideal prerequisite for a retreat into self-contemplation. Anna Karina Sennefelder maps out this topos by analyzing nineteenth century French narrative texts. The range of authors investigated reaches from Senancour, Chateaubriand and Stendhal to Marie d'Agoult and George Sand. The central question is which of otiose leisure's characteristics renders it so suitable for autobiographical self-reflection. What emerges is that in such literature, certain places were considered as particularly apt for experiencing leisure and thus conducive to the success of the narrative retrospective of one's own life. In essence therefore, the main focus is on the profiling and conceptual recording of the »retreats of narration".